Resource Allocation in a Non-convex Economy - Moore, James C.; Whinston, Andrew B.; Wu, Joseph S. (Review of Economic Studies, 1972)
Journal Article Resource Allocation in a Non-convex Economy Get access James C. Moore, James C. Moore Purdue University Search for other works by this author on: Oxford Academic Google Scholar Andrew B. Whinston, Andrew B. Whinston Purdue University Search for other works by this author on: Oxford Academic Google Scholar Joseph S. Wu Joseph S. Wu Purdue University Search for other works by this author on: Oxford Academic Google Scholar The Review of Economic Studies, Volume 39, Issue 3, July 1972, Pages 303–323, https://doi.org/10.2307/2296361 Published: 01 July 1972 Article history Received: 01 April 1971 Revision received: 01 November 1971 Published: 01 July 1972